Analysis of The Meaning of Fasad in The Qur'an as An Ecotheological Critique: An Effort to Reinterpret Islamic Values to The Exploitation of Contemporary Nature - Fatkhunnajah, Emmie; Nugroho, Kharis; AN, Andri Nirwana (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This research aims to analyze the meaning of fasād in the Qur'an as a form of ecotheological criticism of the exploitation of contemporary nature, as well as to reinterpret Islamic values in responding to modern environmental crises. This study departs from the assumption that the meaning of fasād in the interpretation of the Qur'an tends to be limited to the moral and social dimensions, so that its ecological aspects have not been explored optimally. Methodology: The methodology used is qualitative research based on literature studies with a thematic interpretation approach (mawḍū'ī), accompanied by linguistic and ecotheological analysis of the verses of the Qur'an that contain the concept of fasād. The research data is sourced from contemporary interpretive literature and relevant Islamic ecotheological studies. Results: The results of the study show that the fasād in the Qur'an has a multidimensional meaning that includes moral, social, and ecological damage as a result of human deviations in carrying out the caliphate's mandate. The concept of fasād is positioned as a normative critique of human-nature relations that are exploitative and anthropocentric. These findings confirm that the Qur'an offers an ecological ethical framework that emphasizes balance, responsibility, and sustainability. Applications/Originality/Value: The novelty of this research lies in the interpretation of fasād as an ecotheological concept of the Qur'an that reconstructs damage not only morally-socially, but also ecologically, and positions it as an Islamic theological critique of contemporary environmental exploitation through a thematic interpretation approach and linguistic- ecoteological analysis.